2014
DOI: 10.1021/nl504066f
|View full text |Cite
|
Sign up to set email alerts
|

Nearly Exclusive Growth of Small Diameter Semiconducting Single-Wall Carbon Nanotubes from Organic Chemistry Synthetic End-Cap Molecules

Abstract: The inability to synthesize single-wall carbon nanotubes (SWCNTs) possessing uniform electronic properties and chirality represents the major impediment to their widespread applications. Recently, there is growing interest to explore and synthesize well-defined carbon nanostructures, including fullerenes, short nanotubes, and sidewalls of nanotubes, aiming for controlled synthesis of SWCNTs. One noticeable advantage of such processes is that no metal catalysts are used, and the produced nanotubes will be free … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 57 publications
0
98
0
1
Order By: Relevance
“…[83] Zhou reported CNT growth from Scotts (5,5)CNT end-cap 161 (Scheme 45). [84] CNTs were generated from end cap 161,w hich was activated by treatment with air and water at high temperatures.E nd cap 161 was inert to CNT growth reactions without activation. Electrical transport measurements as well as Raman spectroscopy indicated that the resulting CNTs were mainly semiconducting.…”
Section: Cnt Growth From Mixtures Of Segment Structuresmentioning
confidence: 99%
“…[83] Zhou reported CNT growth from Scotts (5,5)CNT end-cap 161 (Scheme 45). [84] CNTs were generated from end cap 161,w hich was activated by treatment with air and water at high temperatures.E nd cap 161 was inert to CNT growth reactions without activation. Electrical transport measurements as well as Raman spectroscopy indicated that the resulting CNTs were mainly semiconducting.…”
Section: Cnt Growth From Mixtures Of Segment Structuresmentioning
confidence: 99%
“…4 These approaches have combined CVD techniques with "amplification" growth, 5,6 cloning, 7,8 catalyst design, [9][10][11][12] and templated organic synthesis. [13][14][15][16][17][18][19][20][21] Of these approaches, catalyst design is arguably the most versatile and accessible method. Recent studies 12 have demonstrated that keeping the catalyst nanoparticle solid during growth is a key factor enabling the production of extremely narrow (n,m) distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Demzufolge wurde nicht nur das theoretisch erwartete (5,5)CNT gebildet, sondern auch CNTs mit anderen Durch-messern. [84] Hier wurden CNTs nach einer aktivierenden Behandlung mit Luft und Wasser unter hohen Te mperaturen aus Endstück 161 erzeugt. [83] Zhou berichtete über ein CNT-Wachstum aus dem (5,5)CNT-Endstück 161 von Scott (Schema 45).…”
Section: Cnt-wachstum Aus Einer Mischung Von Segmentstrukturenunclassified